A legal study on the credit card laws in Malaysia / Nurul Azalea Azarae … [et al.] - Soh, Nabila Veronica; Zainuddin, Nadiatul Liyana; Nanda, Nadia Natasya; Azarae, Nurul Azalea (Faculty of Law, 2013)
This project looks at the relationship between credit card consumers and credit card issuers. The purpose is to show that there are lacunae in law on credit card transactions in Malaysia. Currently, mere guidelines from the Central Bank of Malaysia regulate the transactions. This has been done by conducting legal research and looking at legal reasoning from court decisions , statutes, books, journals, articles, and online internet sources. The lack of law governing credit card transactions causes an imbalance negotiation power between the creditors and credit consumers in Malaysia. Through showing the issues and implications of credit card transaction in Malaysia, this research highlighted the importance of a stronger credit card law and the need to change policies of institutions to be more protective and constructive for consumers.